Economics (Only) Now: The Temporal Limitations of Economics as Part of a Critical Social Studies Pedagogy - Neil Shanks (MDPI AG, 2019)
This study speaks to the limited literature on economics pedagogy as part of a broader, critical, social studies pedagogy. Specifically, it seeks to understand the way that preservice teachers in an urban teaching program conceptualize the function of economics within social studies. Utilizing case study methods and a theoretical framework that intersects critical pedagogical tenets of social analysis with the idea of a counter-hegemonic stance, the study offers insight into the role of economics as part of a broadly critical social studies teacher education program. The results indicate that preservice teachers’ purpose for teaching social studies and the function of economics were aligned in the mission to critically analyze society. However, preservice teachers’ purposes for social studies extended beyond the function of economics into the past, and informed active citizenship for future action. These results show that economics can be a significant part of a social studies education practice that seeks to analyze society, understand the past, and take action for a better future. Unfortunately, limited familiarity and content knowledge inhibit a broader application of the function of economics. Social studies teacher education must purposefully integrate economics content into the exploration of the past and a discussion of future action for justice in order to combat prevailing content knowledge issues in preservice teachers and to help them reconcile their purpose for teaching social studies through economics.